KERJASAMA INDONESIA DAN INTERNATIONAL LABOUR ORGANIZATION (ILO) DALAM PENERAPAN KONVENSI ILO NO. 138 DAN NO. 182 GUNA MENURUNKAN ANGKA PEKERJA ANAK DI BAWAH UMUR PERIODE 2017 - 2019 - Keshia Kamilianingsih, (2021)
Child labor in Indonesia is an issue that attracts a lot of public attention, where in 2017 the percentage of this number has increased after the last 5 years. Therefore, the collaboration between Indonesia and the International Labor Organization (ILO) is considered the right step to address this issue, where ILO introduced ILO Convention No. 138 which regulates the Minimum Age for Employment and ILO Convention No. 182 which regulates the Prohibition and Elimination of the Worst Forms of Child Labour. The presence of these two ILO conventions allows Indonesia to create legal instruments that are considered effective in eradicating the issue of child labour. This study aims to determine the effectiveness of the ILO Convention No. 138 and No. 182 to reduce the number of under age child labour in 2017 - 2019 after Indonesia and ILO established a cooperative relationship. This study uses theory and concepts that can address the issue thoroughly, such as international cooperation theory, international organization concept, and child labour concept. This study also uses a qualitative approach with research methods that include data collection and data analysis. The collected data is divided into primary data in the form of interviews, and secondary data obtained through literature review, news, and articles. The results of this study states that the effectiveness of ILO Convention No. 138 and No. 182 in order to reduce the number of underage child labor in Indonesia has not been fully fulfilled, because the Indonesian people are still unable to apply the values embedded in the two conventions into their daily lives.